International financial management - Eun, Cheol S (McGraw-Hill Irwin, 2009)
Includes bibliographical references and index; pt. I. Foundations of international financial management. Globalization and the multinational firm ; International monetary system ; Balance of payments ; Corporate governance around the world -- pt. II. The foreign Exchange Market, exchange rate determination, and currency derivatives. The Market for Foreign Exchange ; International parity relationships and forecasting foreign exchange rates ; Futures and options on foreign exchange -- pt. III. Foreign exchange exposure and management. Management of transaction exposure ; Management of economic exposure ; Management of translation exposure -- pt. IV. World financial markets and institutions. International banking and money market ; International bond market ; International equity markets ; Interest rate and currency swaps ; International portfolio investments -- pt. V. Financial management of the multinational firm. Foreign direct investment and cross-border acquisitions ; International capital structure and the cost of capital ; International capital budgeting ; Multinational cash management ; International trade finance ; International tax environment and transfer pricing